Directors’ Duties of Care, Skill and Diligence: An Analysis of Some Developments in Malaysia - Balan, Sujata; Guan, Saw Tiong; Tan, Sarah Yen Ling (Journal of Malaysian and Comparative Law, 2018)
In 2007, the Malaysian Companies Act 1965 was amended to incorporate new provisions to deal with directors’ duties of care, skill, and diligence and their powers of delegation and reliance on information provided by others. In addition, a ‘business judgment rule’ was inserted into the Act. This article examines, from the Malaysian perspective, the origins of these novel provisions, their contents, the need for enacting them and their likely impact on business processes and managerial decisions made by company directors in Malaysia.